Integrating bloxberg's Proof of Existence Service With MATLAB - Wittek, Kevin; Krakau, Dominik; Wittek, Neslihan; Lawton, James; Pohlmann, Norbert (Frontiers in Blockchain, 2020)
Proof of Existence as a blockchain service has first been published in 2013 as a public notary service on the Bitcoin network and can be used to verify the existence of a particular file in a specific point of time without sharing the file or its content itself. This service is also available on the Ethereum based bloxberg network, a decentralized research infrastructure that is governed, operated and developed by an international consortium of research facilities. Since it is desirable to integrate the creation of this proof tightly into the research workflow, namely the acquisition and processing of research data, we show a simple to integrate MATLAB extension based solution with the concept being applicable to other programming languages and environments as well.